Application of User Centered Design Method on UI/UX of Indodax Cryptocurrency Exchange Application in Indonesia - UBAIDILLAH, M FATIH FADLIL; Indriyanti, Aries Dwi (Universitas Negeri Surabaya, 2025)
This research aims to improve the quality of the User Interface (UI) and User Experience (UX) of the Indodax cryptocurrency exchange application in Indonesia through the application of the User-Centered Design (UCD) method, against the background of the rapid development of digital technology and the increasing public interest in cryptocurrency. Indodax, as one of the leading platforms in Indonesia, needs to ensure that the UI and UX of its application are able to meet user needs. This research identifies various problems with Indodax's UI and UX through literature studies and user surveys, which are then followed by application redesign using the UCD approach, including understanding the context of use, determining user needs, designing solutions, and evaluating these solutions. The results show that the application of the UCD method has significantly improved user satisfaction, which is reflected in the increase in the System Usability Scale (SUS) score from 56.6 (grade D) to 80.3 (grade B). The findings make an important contribution to the development of more humanistic and user-centered cryptocurrency applications, and can serve as a reference for similar application developers in Indonesia, which is expected to improve the overall competitiveness of cryptocurrency platforms.